The Effect of Social Support and Self Efficacy on The Performance of Youth Swimmers - Tri Novrianti Wahyu Ningsih; Komarudin; Mona Fiametta Febrianty (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2026)
Background : In competitive sports, athletes rely not only on physical strength but also on mental resilience. Low levels of social support and self-efficacy among athletes can lead them to doubt their own abilities. This uncertainty hinders performance, making it difficult for athletes to reach their full potential. This research is crucial because support from coaches, family, and friends can guide athletes in building self-efficacy and improving their performance. Purvouse : This study aims to determine the significant effect of social support and self-efficacy on the swimming performance of adolescent athletes. Methods : The researchers used a quantitative descriptive method with a correlation approach and found that 11 athletes met the criteria. Measurement tool used was the MSPSS questionnaire with a validity value of 0.81 to 0.98 and reliability of 0.92 to 0.94, the GSE questionnaire with a validity value of 0.76 and reliability of 0.90, and performance assessment using a pre-provided judgment assessment rubric without conducting any training or treatment interventions, with only one data collection. Results : The results of the study indicate that social support and self-efficacy have a significant influence of 0.00 < 0.05 on athlete performance. Findings and Novelty : Although many previous studies have addressed social support and self-efficacy, the majority of these studies focused on academic settings in other countries. Furthermore, focus on regional athletes is often overlooked, even though athletes at the regional level may face different challenges compared to those in major cities.